Pengaruh Kompetensi Pedagogik dan Kemandirian Terhadap Pengembangan Profesionalisme Guru Madrasah Tsanawiyah di Kabupaten Aceh Tamiang - Febrian, M Agil; Halimah, Siti; Budianti, Yusnaili (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2025)
Teacher professionalism has long been recognised as a key pillar in improving the quality of education, particularly in the context of achieving the Sustainable Development Goals (SDGs) for 2025–2045. However, in Indonesia, teacher quality remains a serious challenge, with the majority of teachers failing to meet pedagogical competency standards and having limited independence in self-development. Academically, it is important to examine the relationship between pedagogical competence and autonomy because this provides a multidimensional understanding of teacher professionalism, especially in the context of Islamic education, such as Madrasah Tsanawiyah, which has been relatively understudied. This study aims to analyse the influence of pedagogical competence and autonomy on the professional development of Madrasah Tsanawiyah teachers in Aceh Tamiang Regency. The study used a quantitative correlational approach with a sample of 41 teachers selected randomly. Data were collected through Likert-scale questionnaires, classroom observations, and documentation, then analysed using multiple linear regression and SEM-PLS to enhance the model's validity. The results indicate that pedagogical competence has a strong and significant influence on teacher professionalism (β = 0.675; p < 0.001), while autonomy also contributes positively, albeit to a lesser extent (β = 0.117; p = 0.049). Simultaneously, both variables explain 92.9% of the variation in teacher professionalism, confirming the complementary roles of technical and personal aspects. Theoretically, this study enriches the literature by confirming that teacher professionalism is a multidimensional construct. Practically, the results emphasise the importance of policies and training programs that balance the improvement of pedagogical competence with the strengthening of autonomy to enhance the quality of Islamic education in Indonesia.